Anti-Asian Racism during COVID-19: Emotional Challenges, Coping, and Implications for Asian American History Teaching - Xinwei Zhang; Anu Sachdev; Nino Dzotsenidze; Xiaoran Yu; Peggy A. Kong (Education Sciences, 2023)
Anti-Asian scapegoating, sentiment, and hate have caused devastating psychological and behavioral challenges among Asians and Asian Americans during the COVID-19 pandemic. This case study aims to understand Asians’ and Asian Americans’ experiences of racial discrimination during the pandemic, examine their reflections on the impacts of anti-Asian racism on their emotions and coping, and explore their perspectives on teaching Asian American history in combating anti-Asian racism. The results of this study showed that the participants articulated an array of profound emotional challenges in response to the deleterious effects of personal and vicarious experiences of racism. They used varied coping strategies, exhibiting heightened vigilance and intentional proactive measures to protect themselves and their communities against anti-Asian racism. The participants also underscored the intersectionality between race and gender, highlighting the vulnerability of Asian women. Additionally, the participants advocated for the inclusion of Asian American history in the school curriculum to dismantle and disrupt systematic racism. This study reveals the emotional and behavioral effects of anti-Asian racism on Asian and Asian American individuals and communities. It illustrates the crucial role of amplifying Asian and Asian American voices in the school curriculum in combating anti-Asian racism beyond the pandemic.